Genetic diversity and differentiation of Acanthoscelides obtectus Say (Coleoptera: Bruchidae) populations in China. (26th October 2016) - Duan, Canxing; Zhu, Zhendong; Li, Wanchang; Bao, Shiying; Wang, Xiaoming
Abstract: Bean weevil Acanthoscelides obtectus Say is one of the most destructive pests of bean seeds. Using 10 microsatellite loci, we studied the genetic diversity and differentiation of 13 geographical populations. A total of 79 alleles were detected, with an average of 7.900 alleles per locus. The gene flow and genetic differentiation rate values at the 10 loci varied from 0.376 to 1.560 and 13.8–39.9%, with averages of 0.774% and 24.4%, respectively. Among the 13 populations, the effective number of alleles and observed heterozygosity ranged from 1.865 to 2.848 and 0.457 to 0.646, respectively. Shannon's information index ranged from 0.684 to 1.104. In all comparisons, the fixation index ( FST ) values ranged from 0.021 to 0.463, with a total FST value of 0.228 among the 13 populations, indicating a moderate level of genetic differentiation among these populations. Analysis of molecular variance revealed that the genetic variation within populations accounted for 67.7% of the total genetic variation. Using the unweighted pair group method with arithmetic mean cluster analysis, 13 populations were clustered into three distinct genetic groups. The pattern of the three concentrated groups from principal component analysis showed a similar result to cluster, although some individuals interpenetrated with one another.